The Effect of Sacred Lotus (Nelumbo nucifera) and Its Mixtures on Phenolic Profiles, Antioxidant Activities, and Inhibitions of the Key Enzymes Relevant to Alzheimer’s Disease - Piya Temviriyanukul; Varittha Sritalahareuthai; Natnicha Promyos; Sirinapa Thangsiri; Kanchana Pruesapan; Wanwisa Srinuanchai; Onanong Nuchuchua; Dalad Siriwan; Nattira On-nom; Uthaiwan Suttisansanee (Molecules, 2020)
Sacred lotus (Nelumbo nucifera) has long been used as a food source and ingredient for traditional herbal remedies. Plant parts contain neuroprotective agents that interact with specific targets to inhibit Alzheimer’s disease (AD). Organic solvents including methanol, ethyl acetate, hexane, and n-butanol, are widely employed for extraction of sacred lotus but impact food safety. Seed embryo, flower stalk, stamen, old leaf, petal, and leaf stalk of sacred lotus were extracted using hot water (aqueous extraction). The extractions were analyzed for their bioactive constituents, antioxidant and anti-AD properties as key enzyme inhibitory activities toward acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and β-secretase 1 (BACE-1). Results showed that the sacred lotus stamen exhibited significant amounts of phenolics, including phenolic acids and flavonoids, that contributed to high antioxidant activity via both single electron transfer (SET) and hydrogen atom transfer (HAT) mechanisms, with anti-AChE, anti-BChE, and anti-BACE-1 activities. To enhance utilization of other sacred lotus parts, a combination of stamen, old leaf and petal as the three sacred lotus plant components with the highest phenolic contents, antioxidant activities, and enzyme inhibitory properties was analyzed. Antagonist interaction was observed, possibly from flavonoids–flavonoids interaction. Further in-depth elucidation of this issue is required. Findings demonstrated that an aqueous extract of the stamen has potential for application as a functional food to mitigate the onset of Alzheimer’s disease.